Legal Consequences of Selling Expired Snack Products by Changing the Production Date Label Conducted by Business Actors - Syaus, Fanisa Oktaviani; Abdussamad, Zamroni; Elfikri, Nurul Fazri (Estudiante Law Journal, 2024)
The purpose of this study is to describe the legal consequences of the sale of expired snack products by changing the production date label carried out by business actors. The research method used in this article uses normative research methods by conducting a library study approach. The results of this study are the case of changing the expiration date label on food packaging, as well as other regulations that are relevant to the case, namely Permendag No.25 of 2021 concerning the Determination of Goods that are Required to Use or Equip Indonesian Language Labels and PP No.69 of 1999 concerning Food Labels and Advertising. In MOT 25/2021, it is explained in Article 1 Paragraph (1) that, with this Ministerial Regulation, goods that are obliged to use or complete Indonesian language labels are determined. Then in Article 2 Paragraph (1) of Government Regulation of the Republic of Indonesia Number 69 of 1999 concerning Food Labels and Advertising, it is stated that, Every person who produces or imports packaged food into the territory of Indonesia for trading is obliged to include a label on, in, and or in food packaging. So, from the explanation above that the use of labels on food products is very important because it provides clear information about the product, whether it is still suitable for consumption or not, so the use of labels must be included. therefore, the replacement of production and expiration date labels on snack and snack food packaging can have a negative impact on society, especially on children who often consume these foods. This can also jeopardize human safety and health, in accordance with the principle of consumer safety and security, which ensures that people can use, use, and use the goods or services they consume or use.